Uma Avaliação das Arquiteturas para Interoperabilidade entre Objetos - Cerqueira, Renato; Ierusalimschy, Roberto (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 1996)
This paper studies some issues related to interoperability of object-oriented languages. First, it discusses the relationship between the development of software components for reuse and the object interoperability issue. After this discussion, it presents some aspects that make difficult this interoperability among objects defined in different languages and also among distributed objects, and the main proposals to solve the interoperability problem. Finaly, it does an analysis of the practical application of the main interoperability frameworks. This analysis has been based on a case study, and has tried to identify the main failures of studied frameworks and their possible evolution.